DETERMINING THE AMOUNT OF ELECTRONIC SCINTILLATIONS OF ELECTRO – OPTIC TRANSFORMER OF IMAGES: DETERMINING THE AMOUNT OF ELECTRONIC SCINTILLATIONS OF ELECTRO – OPTIC TRANSFORMER OF IMAGES - Getsov, Petar; Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
One of the basic requirements when using electro - optical transformer (EOT) of images in space research [1, 2, 5, 7, 8] is the low level of bright light flashes on the screen, called multi - electronic scintillations. The existence of multi - electronic scintillations leads to significant expansion of the possibility for diminishing the utmost sensitivity of the EOT [4, 6, 9, and 10]. The definition of the amount of scintillations per definite time could be done with the help of the method for scintillations' calculation while using photo - electronic multiplier [3]. If the number of scintillations' distribution over the active surface of the screen is determined and experimentally are evaluated the distribution parameters for a certain EOT, it is a matter of simpler methods required for the scintillation evaluation without the need for development of complex scanning devices. The current research is about evaluating the law of scintillations' amount distribution over the active surface of the screen, evaluation of their amplitude spectrum and development of method for defining the amount of multi - electronic scintillations over the active surface of the EOT's screen.